Developing comprehension in young readers lesson plans from RAP Conventions - Ocampo, Dina (Anvil, 2008)
"Developing comprehension in young readers: lesson plans from RAP Conventions (Volume 1) is a compilation of the best demonstration lesson plans in early literacy development presented during our 2007 Annual Convention in April held in St. Paul's College in Pasig City and the Midyear Demofest in October 2007 in University of St. La Salle in Bacolod City. This book was conceived as another affirmative response to one of the needs of the reading teachers -- accessibility of developmentally appropriate lessons in English and in Filipino which could directly be used in the classrooms, and which could be used as models by the reading teachers in developing their own lessons." --Back cover.